Clinical features and aggravating factors in nummular eczema in Thais - Sukhum Jiamton (2018)
Background: Nummular eczema is an idiopathic inflammatory skin disease that mostly has a chronic and relapsing course. Many factors are thought to be responsible for this condition, such as atopic dermatitis, dry skin, emotional stress or seasonal variation. Objective: The purpose of the study was to assess clinical findings and aggravating factors of nummular eczema and to evaluate characteristics, severity of disease and quality of life of patients. Methods: One hundred patients aged from 18 years old diagnosed as nummular eczema were asked about general data, characteristics and clinical findings of nummular eczema, and completed the Thai version of the Dermatology Life Quality Index (DLQI) questionnaires. They also underwent a physical examination. Results: Mean (SD) age was 42.1 (18.4) years and two-thirds were women. Fourteen percent had history of atopic dermatitis and half had history of atopy or contact dermatitis. From patch tests, the most common allergen was found to be nickel. Ninety percent of lesions located in lower extremities and two-thirds had a co-existing dryness of the skin. Emotional stress and drinking alcohol aggravated the disease. Those who had exacerbation in summer or skin dryness tended to have persisting disease. Mean(SD) total DLQI score among our patients was 9.2(6.8). Quality of life of the patients was significantly impaired in younger life, office workers, those with trunk-distributed lesions and those having extensive lesions. Conclusions: Clinical features and possible aggravating factors of nummular eczema were reported. The result confirmed the chronic course of the disease. The nummular eczema affected quality of life of patients and itching caused the most impairment.